Mixed two fields finite element formulation for flexible pavement - Jha, Kaushal Kumar (Nepalese Journal of Engineering, 2005)
This paper aims to analyze a flexible pavement structure using mixed two fields finite element method. Both displacements as well as stresses are considered nodal unknowns in the proposed method. The advantage of this method is that stresses are directly obtained from the single step of computation. In conventional finite element method, stress components are computed from nodal displacements at Gauss points. Two examples are presented in order to validate the proposed model and the results are compared with exact solutions. Satisfactory results are obtained in either case. Keywords: pavement, finite element, axisymmetric. Nepalese Journal of Engineering Vol.1(1) 2005 pp.64-69